2016
DOI: 10.1155/2016/4158567
|View full text |Cite
|
Sign up to set email alerts
|

A 26-Year-Old Female with Systemic Mastocytosis with Associated Myeloid Neoplasm with Eosinophilia and Abnormalities ofPDGFRB, t(4;5)(q21;q33)

Abstract: Various translocations involving the PDGFRB gene are identified in myeloid neoplasms. However, the PRKG2/PDGFRB fusion gene associated with t(4;5)(q21;q33) has previously been reported in only 3 patients. We present the case of a 26-year-old woman with microcytic anemia, basophilia, thrombocytosis, and massive splenomegaly, who was found to have systemic mastocytosis and associated clonal hematological non-mast cell lineage disease (SM-AHNMD), with myeloid neoplasm with PRKG2/PDGFRB rearrangement. Initial find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…We found that the BM specimens from these patients were abnormal, with frequent hypercellularity (90% cases), abnormal megakaryocytes with either MDS, MPN or mixed MDS/MPN features, significant fibrosis, and, less frequently, dysgranulopoiesis, dyserythropoiesis, and abnormal eosinophils. Similarly to what is seen in PDGFRA ‐rearranged neoplasms, proliferation of mast cells with aberrant CD25 expression 33,34 was frequent, being detected in three of five cases with mast cell work‐up performed, with one case fulfilling the diagnostic criteria for systemic mastocytosis. Interestingly, none of the three B‐ALL cases with PDGFRB rearrangement had eosinophilia, monocytosis, or morphological or immunophenotypic features that could distinguish them from other B‐ALL cases.…”
Section: Discussionmentioning
confidence: 53%
“…We found that the BM specimens from these patients were abnormal, with frequent hypercellularity (90% cases), abnormal megakaryocytes with either MDS, MPN or mixed MDS/MPN features, significant fibrosis, and, less frequently, dysgranulopoiesis, dyserythropoiesis, and abnormal eosinophils. Similarly to what is seen in PDGFRA ‐rearranged neoplasms, proliferation of mast cells with aberrant CD25 expression 33,34 was frequent, being detected in three of five cases with mast cell work‐up performed, with one case fulfilling the diagnostic criteria for systemic mastocytosis. Interestingly, none of the three B‐ALL cases with PDGFRB rearrangement had eosinophilia, monocytosis, or morphological or immunophenotypic features that could distinguish them from other B‐ALL cases.…”
Section: Discussionmentioning
confidence: 53%
“…Up to 40% of all SM cases are associated with another hematological disease, which rarely can be a myeloid/lymphoid neoplasm with eosinophilia ( 2 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilia (≥1.5x10 9 /L) is one of the most common features of these neoplasms. In the subgroup associated with PDGFRA rearrangement, the most common genetic abnormality is the FIP1L1-PDGFRA gene fusion, caused by 4q12 deletion (Figure 1) (1,(4)(5)(6). Patients frequently complain of fatigue, pruritus, and symptoms related to eosinophilic infiltrates in different organs; splenomegaly and hepatomegaly are common findings (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the MC proliferation may form dense clusters, showing histopathological features reminiscent of SM. 16,[18][19][20][21] Such cases often have accompanying eosinophilia and are often diagnosed as SM-AMN before the detection of the TK fusion. Some characteristic histopathological features have been observed in association with certain specific fusion genes.…”
Section: Histopathologymentioning
confidence: 99%
“…Atypical MCs either spindle or round, with aberrant CD25 expression, scattered and in loose aggregates, were initially described as a feature characteristic of PDGFRA rearranged cases, but have subsequently been reported in cases with other TK gene rearrangements. In some cases, the MC proliferation may form dense clusters, showing histopathological features reminiscent of SM 16,18–21 . Such cases often have accompanying eosinophilia and are often diagnosed as SM‐AMN before the detection of the TK fusion.…”
Section: Eosinophilic Disordersmentioning
confidence: 99%